Amorphous FeOOH Oxygen Evolution Reaction Catalyst for Photoelectrochemical Water Splitting - Chemelewski, William D; Lee, Heung-Chan; Lin, Jung-Fu; Bard, Allen J; Mullins, C. Buddie (Journal of the American Chemical Society, 2014)
Reaching the goal of economical photoelectrochemical (PEC) water splitting will likely require the combination of efficient solar absorbers with high activity electrocatalysts for the hydrogen and oxygen evolution reactions (HER and OER). Toward this goal, we synthesized an amorphous FeOOH (a-FeOOH) phase that has not previously been studied as an OER catalyst. The a-FeOOH films show activity comparable to that of another OER cocatalyst, Co-borate (Co–Bi), in 1 M Na2CO3, reaching 10 mA/cm2 at an overpotential of ∼550 mV for 10 nm thick films. Additionally, the a-FeOOH thin films absorb less than 3% of the solar photons (AM1.5G) with energy greater than 1.9 eV, are homogeneous over large areas, and act as a protective layer separating the solution from the solar absorber. The utility of a-FeOOH in a realistic system is tested by depositing on amorphous Si triple junction solar cells with a photovoltaic efficiency of 6.8%. The resulting a-FeOOH/a-Si devices achieve a total water splitting efficiency of 4.3% at 0 V vs RHE in a three-electrode configuration and show no decrease in efficiency over the course of 4 h.